Bangladesh in the new millennium : a University of Dhaka study - Abul Kalam; University of Dhaka (Dhaka : University Press, 2004)
Contributed articles, chiefly on the economic conditions and a few on political situation in Bangladesh.
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: Bangladesh -- Economic conditions -- 21st century; Bangladesh -- Politics and government -- 21st century